Relationship between MDQ scores of menstrual-associated symptoms and lifestyle in female judo athletes - Itaka, T.; Fujihira, K.; Okawa, Y.; Miyazaki, S.; Tsukada, M. (Rigakuryoho Kagaku, 2022)
Purpose: This study aimed to clarify the relationship between menstrual-associated symptoms and lifestyle in female judo athletes by menstrual period. Participants and Methods: One hundred sixty-nine female judo players aged 18 to 21 years were surveyed using a questionnaire consisting of profile, judo practice, and lifestyle, and a questionnaire on menstruation-related symptoms (MDQ). Results: The results showed a negative correlation between the total score of the MDQ before and during menstruation and the amount of sleep on weekdays. Female judo players who slept less on weekdays showed higher scores of menstrual-associated symptoms. Conclusion: Since female judo players show worsening of menstrual symptoms before and during menstruation, it is necessary to review their lifestyle, including sleep duration.